Perencanaan Arsitektur Enterprise Berbasis Cloud Computing Menggunakan Togaf (Studi Kasus: PT. XYZ) - Mokhamad Wahidin (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2018)
PT. XYZ is a manufacturing company engaged in the production of tires. Good business strategy is necessary for the company to compete with local competitors as well as with other companies in the group XYZ. Business strategy is also needed in order to achieve its goal in providing the best services for customers. Support the implementation of information systems and information technology is needed to support the company's business strategy. Planning of the Enterprise Architecture is necessary for the company to run its business processes. Enterprise architecture is composed of the Business Architecture, Data Architecture, Application Architecture and Technology Architecture. Business processes and organizational activities executed using the data collected, managed, secured and distributed using applications, both custom applications and common applications that run over the technology infrastructure and computer networks. The research report in this thesis discusses about planning the Enterprise Architecture of Manufacturing Information System Architecture Based Cloud Computing using TOGAF, a case study in PT.XYZ. In planning this architecture using the TOGAF-ADM to pass the following stages: Defining planning the Architecture Vision, Planning the Business Architecture, Planning the Information System Architecture, Planning the Technology Architecture, Solutions and Opportunities, Migration Planning, Implementation Management, and Change Management Architecture. The research process is done by looking at the business strategy on the manufacturing process and products distribution from PT. XYZ. The results of this study are planning the enterprise architecture of manufacturing information system at PT. XYZ to support the implementation of enterprise information systems as a whole, to solve the integration problems of information systems, and improve effectiveness and efficiency in the implementation of information technology infrastructure.